Benghal Dayflower/Tropical Spiderwort (Commelina benghalensis L.) Identification and Control - Jay A. Ferrell; Greg E. MacDonald; Pratap Devkota (EDIS, 2020)
This 3-page document provides an overview of tropical spiderwort identification and control. Written by J. A. Ferrell, G. E. MacDonald, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised May 2020.